On network flow equations and splitting formulas for Sojourn times in queueing networks. (1991) - Daduna, Hans
Abstract : LEMOINE's network flow equations are generalized to the case of multiserver networks. These equations provide a basis for recursive evaluation of residual conditional sojourn time moments.